Hale-Bopp and handedness: Individual differences in memory for orientation - Martin, M; Jones, G (1999)
The accuracy with which a person recalls the orientation of a human figure or head has been shown to depend systematically on the person's handedness. This study investigated whether memory for the orientation of an inanimate object displays a similar effect. In contrast to previous work investigating memory for depictions encountered over many years, the present work focused on memory for a unique event that engaged considerable attention over a relatively brief period - Comet Hale-Bopp. The results showed that although right-handed and left-handed individuals did not differ in their memory for semantic information concerning the comet, they did differ in their memory for its orientation. Right-handed people were significantly more likely than left-handed people both to recall and to recognize the comet as facing to the left. The results suggest that memory performance may be influenced by patterns of underlying cerebral motor activation.